Management of human resources in national defense depend on defense economics point of view - Ratih Rachma Kurnia; Guntur Eko Saputro; Sri Murtiana (International Journal on Social Science, Economics and Art, 2023)
Indonesia is a country with abundant human resources but the number of military forces does not match with population and area. This paper aims to explain how the role of human resources as the main in the country's defense efforts to support the national economy because human resources (HR) is the most crucial resource and the element that determines the development of civilization, including the aspect of national defense. The method used is a descriptive qualitative method with a literature study research approach by collecting information from journals, books, and other media to obtain topic-related materials. The result of this writing is that it can be concluded that the competence of a systematic and professional state defense management and implementation system is necessary to face threats to state defense,  it is necessary to develop the strength and capabilities of state defense including the development of human resources, natural resources, artificial resources, facilities and infrastructure, technology, and defense industry as well as a value system to improve capabilities defense of the country and support the national economy.